(untitled) (Global Scientific Review, 2022)
This article analysis the increasing numbers of professional terms of winter sports. By its linguocognitive and linguoculturological characteristics, a term is a unit similar to a word used in a specific field, and it is used to denominate concepts, which belong to specific areas and fields of activity. It could therefore be said that a term is a word or several words, which define or denominate a concept from science, technique and its basic characteristics would be precision and the ability to define